Comparative analysis of outcomes after liver resection and liver transplantation for early stages hepatocellular carcinoma in HIV-infected patients. An intention-to-treat analysis. Issue 6 (June 2020) - Golse, Nicolas; Duarte, Pablo; Fontana, Andrea; Bündchen, Cristiane; Karam, Vincent; Allard, M.-A.; Pittau, Gabriella; Ciacio, Oriana; Duclos-Vallée, J.-C.; Sa Cunha, A.; Castaing, Denis; Cherqui, Daniel; et al.
Abstract: Background: To address the results of resection for hepatocellular carcinoma (HCC) in human immunodeficiency virus (HIV)-carriers, and to compare them against survival after liver transplantation (LT). Methods: All patients with HIV and HCC listed for LT (candidates = LTc+) or resection (LR+) between 2000 and 2017 in our centre were analysed and compared for overall survival (OS) and disease-free survival (DFS). Results: The LTc + group (n = 43) presented with higher MELD scores and more advanced portal hypertension and HCC stages than LR + group (n = 15). One-, 3- and 5-year intention-to-treat survival rates were: 81%, 60% and 44%, versus 86%, 58% and 58% in the LTc+ and LR + groups, respectively (p = 0.746). Eleven LTc + patients dropped out. After LT, OS was 81%, 68% and 59% (no difference with LR + group; p = 0.844). There tended to be better DFS after LT, reaching 78%, 68% and 56% versus 53%, 33% and 33% in the LR + group (p = 0.062). Conclusion: This was the largest series of resections for HCC in HIV + patients and the first intention-to-treat analysis. Although LT and resection do not always concern the same population, they enable equivalent survival. At the price of higher recurrence rate, resection could be integrated in the global armoury of liver surgeons.